Special aspects of the clinical course and replacement therapy peculiarities in a patient with autoimmune polyglandular syndrome type 1: a clinical case - Maria G. Pavlova; Olga O. Golounina; Tatyana B. Morgunova; Natalya V. Likhodey; Marina F. Kalashnikova; Aleksandr G. Farmanov; Tamriko D. Khazaliya; Valentin V. Fadeev (Alʹmanah Kliničeskoj Mediciny)
Autoimmune polyglandular syndrome type 1 (APS-1) is an extremely rare monogenic autosomal recessive disease characterized by development of multiple organ failure with predominant endocrine glands involvement. The challenges of patient management are related to low adherence to the lifelong multicomponent therapy, high risk of complications, including pneumonia, adrenal insufficiency decompensation, necrotic colitis and other acute infectious and inflammatory diseases. Due to the rarity of this disorder, clinicians lack sufficient experience with management of such patients, which could lead to delayed medical care and patient death.